COGNITIVE DYSFUNCTION IN PATIENTS WITH ATRIAL FIBRILLATION: ASSESSING THE ROLE OF VASCULAR FACTORS - E. S. Derevnina; N. S. Akimova; D. G. Persashvili; Yu. G. Schwartz (Кардиоваскулярная терапия и профилактика)
Aim. To study the association between the presence and type of atrial fibrillation (AF), cognitive dysfunction, and brachiocephalic artery pathology.Material and methods. In total, 54 patients with AF and 20 AF-free patients who had Functional Class I–III chronic heart failure (CHF) underwent cognitive assessment tests, echocardiography, cerebral nuclear magnetic resonance imaging, and duplex brachiocephalic ultrasound.Results. In AF patients, deteriorated parameters of memory and attention were registered. Patients with persistent AF demonstrated worse cognitive function parameters. The characteristics of short-term memory and attention, attainment of visual and motoric skills, and attention shift and span were not associated with the intima-media thickness of common carotid artery and its bifurcation.Conclusion. There is an association between the presence of AF, its type, and the severity of cognitive dysfunction, which is independent of the degree of brachiocephalic artery abnormalities.